(untitled) (Interdisciplinary Studies Journal, 2026)
Education is experiencing the impacts of using educational intelligences in the classroom, which can lead to promising results in acquisition of new methodologies and learning. The collaboration between teachers and artificial intelligence can create opportunities for teaching and learning. To control some effects, the teacher’s intervention based on well-established interpersonal and strategic skills can be a first step in their preparation to face the impact of artificial intelligence systems on educational activities. In this sense, a partnership for teacher training regarding the use of Artificial Intelligence in education was established by the Faculty of the State of São Paulo, the University of the State of Paraná, and the Education Department of a city Paulista. The intention is to enable the exchange of experiences between Higher Education and the teachers of the city, to provide the improvement and training of educators using artificial intelligence, rethinking pedagogical practices, and teaching subjects. With a focus on free and accessible solutions, the teacher will learn to integrate AI into planning, material production, personalized teaching, assessments, and teaching routines.